Circuit Implementation, Operation, and Simulation of Multivalued Nonvolatile Static Random Access Memory Using a Resistivity Change Device - Kazuya Nakayama; Akio Kitagawa (Active and Passive Electronic Components)
We proposed and computationally analyzed a multivalued, nonvolatile SRAM using a ReRAM. Two reference resistors and a programmable resistor are connected to the storage nodes of a standard SRAM cell. The proposed 9T3R MNV-SRAM cell can store 2 bits of memory. In the storing operation, the recall operation and the successive decision operation of whether or not write pulse is required can be performed simultaneously. Therefore, the duration of the decision operation and the circuit are not required when using the proposed scheme. In order to realize a stable recall operation, a certain current (or voltage) is applied to the cell before the power supply is turned on. To investigate the process variation tolerance and the accuracy of programmed resistance, we simulated the effect of variations in the width of the transistor of the proposed MNV-SRAM cell, the resistance of the programmable resistor, and the power supply voltage with 180 nm 3.3 V CMOS HSPICE device models.